Hydrogen production through sorption-enhanced steam reforming of ethanol using CaO-based sorbent mixed with iron oxide catalyst - Elfaki, Hind Omer Elsheikh (2016)
Novel synthetic CaO-based sorbents for carbon dioxide (CO2) capture in sorption-enhanced steam reforming (SESR) were prepared by the co-precipitation method. Magnesium oxide (MgO) and cerium oxide (CeO2) were mixed with calcium oxide (CaO) in different molar percentages in order to obtain the optimum percentage, which provide high CO2 uptake capacity and cyclic stability. The TGA results for CO2 uptake, revealed that for the molar ratio of CaO, MgO and CeO2 of (6:2:1) and (4:2:1), the sorbents had CO2 capture capacity of 29 and 25 wt.%, respectively.